Conservation status assessment of the highest forests in the world: Polylepis flavipila forests as a case study - Ames-Martínez, F.N. (2021)
Polylepis forests are one of the most threatened high Andean ecosystems, with 15 species and eight subspecies being categorized as critically endangered, vulnerable or near threatened by IUCN. However, their conservation status is poorly evaluated and could be outdated. As a case study, we evaluated Polylepis flavipila, a species endemic to the Peruvian central Andes, that is categorized as Vulnerable in Peru and is not mentioned in the Global Threatened Species Red List. We used two methods to categorize P. flavipila: (1) a species-level assessment using criteria proposed by IUCN and (2) a population-level assessment of four forests using the more specific criteria proposed by Navarro and collaborators. We recorded 350 relicts of P. flavipila forests as identified from herbariums and other sources. Forest cover was reduced 53% over 45 years as evaluated using satellite images from 1975 and 2020 and we estimated a total area of 458 and 216 km2, respectively. Thus, according to the IUCN criteria, P. flavipila should be classified as Endangered. At the population level, the application of the criteria of Navarro and collaborators results in different threat categories: one of the studied forests is classified as Critically Endangered, two forests as Vulnerable and one as Least Concern. We stress the need for updated categorizations for the 45 described Polylepis tree and shrub species based on the following facts: the only species we tested should change category, the IUCN categorizations were performed 16 to 22 years ago, and there have been many changes in the taxonomy of the genus. The assessment using IUCN criteria should also be complemented with more detailed evaluations at the population level since important differences were detected at a smaller scale, which could help target conservation and restoration resources more efficiently.